The “g” in Faking: Doublethink the Validity of Personality Self-Report Measures for Applicant Selection - Geiger, Mattis; Olderbak, Sally; Sauter, Ramona; Wilhelm, Oliver (Frontiers in Psychology, 2018)
The meta-analytic finding that faking does not affect the criterion validity of self-report measures in applicant selection suggests cognitive abilities are crucial to fake personality to an expected optimal profile in self-report measures. Previous studies in this field typically focus on how the extent of faking changes self-report measurement. However, the effect of faking ability is rarely considered. In Study 1 (n = 151), we link two questionnaires, the WSQ and the NEO-PI-R, to use them for later faking ability task. With O*NET expert ratings and the linked questionnaires we establish veridical responses of optimal personality profiles for both questionnaires. Based on this, in Study 2, we develop six faking ability task employing both questionnaires and three common jobs to fake for. To score the tasks, we introduce profile similarity metrics that compare faked response vectors to optimal profile vectors. The faking ability tasks were administered to a community sample (n = 210) who additionally completed measures of cognitive abilities, namely general mental ability, crystallized intelligence and interpersonal abilities. For all, based on previous research, it can be argued that they should predict individual differences in faking ability. We establish a measurement model of faking ability and its relation to the other cognitive abilities. Using structural equations modeling, we find the strongest effect for crystallized intelligence and weaker effects for general mental ability and interpersonal abilities, all positively predicting faking ability. We show for the first time that we can measure faking ability with psychometrically sound techniques establish a confirmatory factor model of faking ability and that it is largely explained by other cognitive abilities. We conclude that research supporting a positive link between self-reported personality and job performance is presumably confounded by cognitive abilities, because they are predictive of both faking self-reported personality and job performance. We recommend researchers to broaden their measurements with assessments of faking ability or other cognitive abilities (besides general mental ability) in research regarding applicant selection.